PENGARUH BUDAYA ETIS ORGANISASI, SISTEM PENGENDALIAN INTERNAL, ASIMETRI INFORMASI DAN KESESUAIAN KOMPENSASI TERHADAP KECURANGAN (Persepsi Pegawai Dinas Di Kabupaten Kepulauan Mentawai) - Hidayat, Zullaika; Sari, Ria Nelly; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the influence of organizational ethical culture, internal control system, information asymmetry and suitability of compensation to fraud. population in this study consisted of 1857 employees, while respondents in the study consisted of 95 employees at the Department of Mentawai Islands. The sampling method used in this research is Convenience Sampling. Data collection using questionnaire. Data were analyzed using SPSS version 21. The result of research shows that there is influence between organizational ethical culture with fraud, there is influence between internal control system and fraud, there is influence between information asymmetry with fraud and there is influence between suitability of compensation with fraud. Based on the research results can be seen that a good ethical organizational culture, an effective internal control system, and appropriate compensation can reduce the fraud action on an agency and the higher level of information asymmetry that occurs in an agency will increase the fraud action on the agency.Keywords : Organizational Ethical Culture, Internal Control System, Information Asymmetry, Compensation suitability, Fraud.